The significance of one versus two styles: the return of Seddera section Socotroseddera to Convolvulus - Luna, Javier A; Demissew, Sebsebe; Darbyshire, Iain; Carine, Mark A (Phytotaxa, 2014)
The generic placement of the Socotran endemic Seddera section Socotroseddera is reassessed. A molecular phylogenetic analysis using the chloroplast matK resolves Seddera as polpyphyletic with samples of Seddera section Socotroseddera resolved within Convolvulus. This placement is congruent with morphology, notably style morphology as the species of this section possess one style, in keeping with Convolvulus and in contrast to other species of Seddera. It also reflects the original generic placement of these species. The return of species of Seddera section Socotroseddera to Convolvulus is proposed. A new combination for a recently described species is necessary to enact this transfer and so is provided.